Justicia zappiana (Acanthaceae), a new species from the Atlantic Forest of Bahia, Brazil - Silva, Fabio Araújo Da; Jardim, Jomar Gomes; Fraga, Claudio Nicoletti De (Phytotaxa, 2026)
Justicia zappiana is described and illustrated as a new species endemic to the Atlantic Forest of Bahia, Brazil. It occurs in the understory of dense rainforests within protected areas in the southern part of the state and shows morphological affinities with J. anagallis and J. lavandulifolia. It is distinguished by subcylindrical stems, very narrow leaves with short petioles, reduced peduncles, shorter filaments, and pubescent capsules with tuberculate seeds. Although occurring in conservation units, the species is known from few localities, with restricted distribution and small populations. For these reasons, it is assessed as Vulnerable (VU) under IUCN criteria. This discovery highlights the importance of field collections in Bahia for advancing knowledge of Acanthaceae diversity and supporting conservation strategies.